Characterization of the novel HLA‐A*01:367 allele by sequencing‐based typing. (17th May 2021) - Cargou, Marine; Elsermans, Vincent; Top, Isabelle; Blouin, Laura; Visentin, Jonathan
Abstract : HLA‐A*01:367 differs from HLA‐A*01:01:01:01 by one nucleotide substitution in codon 271 in exon 4.